The Level of Professional Satisfaction of Teachers for Social Services: A Field Study on The Secondary Schools of The City of Constantine - Mezaouri, Khadidja (Journal of Human Sciences, 2022)
Our study aimed to reveal the level of satisfaction of secondary education teachers on the social services provided by the provincial commission for social services. Where a questionnaire was applied to a sample estimated at 114 secondary education teachers distributed in the secondary schools of Constantine district in the period between January and February 2020 by adopting appropriate statistical methods، so that the study concluded that: • The Level of satisfaction of secondary education teachers on the social services provided by the provincial commission for social services is low. • The seniority variable in education affects the level of satisfaction of the secondary education teachers towards the social services it provides by the provincial commission for social services. • The family status variable affects on the level of satisfaction of the secondary education teachers towards the social services it provides by the provincial commission for social services.